2010
DOI: 10.1177/1359105310364171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Order on Intentions to Undergo Predictive Genetic Testing

Abstract: As predictive genetic testing availability increases so does our need to understand factors associated with test uptake. This study tests whether the order positive and negative information about genetic testing for breast cancer is presented in affects intention to take a genetic test. Eighty-four women were randomly allocated into three groups: (1) positive then negative information; (2) negative then positive information; and (3) a control group. A significant effect was found in relation to perceived risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Threat appraisals may not have predicted intention because the present study used a mostly young adult sample, whose appraisals of disease severity and vulnerability may have been limited by the distal nature of disease risks revealed by WGS screening. This seems unlikely given that other studies (e.g., Morrison et al, 2010) involving young, healthy adult samples found an association between perceived personal risk and intention to undergo genetic testing for a future-onset disease. A more likely explanation comes from Sweeny and Legg (2011), who assert that threat beliefs pertain to specific disease outcomes, and thus do not make sense when screening provides feedback on multiple disease outcomes, as with WGS screening.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Threat appraisals may not have predicted intention because the present study used a mostly young adult sample, whose appraisals of disease severity and vulnerability may have been limited by the distal nature of disease risks revealed by WGS screening. This seems unlikely given that other studies (e.g., Morrison et al, 2010) involving young, healthy adult samples found an association between perceived personal risk and intention to undergo genetic testing for a future-onset disease. A more likely explanation comes from Sweeny and Legg (2011), who assert that threat beliefs pertain to specific disease outcomes, and thus do not make sense when screening provides feedback on multiple disease outcomes, as with WGS screening.…”
Section: Discussionmentioning
confidence: 81%
“…Secondly, participant attitudes and intention were assessed immediately after viewing the information manipulation, with no longer term follow up. Although this design limitation is common in experimental studies (e.g., Morrison et al, 2010), it prevents conclusions about the stability of screeningrelated cognitions and intention over time. Finally, screening intention may not translate into actual uptake.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
See 3 more Smart Citations